Kesadaran WP, Kualitas Pelayanan, Sanksi Pajak dan Penerapan Tapping Box pada Kepatuhan WP Restoran - Bagus Kresna Yudha, Putu Nanda; Ery Setiawan, Putu (E-Jurnal Akuntansi; Vol 30 No 7 (2020), 2020)
This study aims to provide empirical evidence about the influence of taxpayer awareness, service quality, tax sanctions and the application of transaction recording devices (tapping boxes) to taxpayer compliance in paying restaurant taxes. This research was conducted on companies that have been registered with the Denpasar City Revenue Agency since 2017. The sample in this study is a restaurant that has been installed with a taping box. The method of determining the sample using a purposive sampling method using the Slovin formula to obtain 31 companies as samples. Data collection using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of hypothesis testing show that the variable of taxpayer awareness, service quality, tax sanctions, and the application of tapping boxes has a positive effect on the compliance of natural taxpayers paying restaurant taxes at the Denpasar City Revenue Agency. Keywords: Awareness of Taxpayers; Service Quality; Tax Sanctions; The Application Of Tapping boxes; Taxpayer Compliance.